Strategic power indices: Quarrelling in coalitions - László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2008)
While they use the language of game theory known measures of a priory voting power are hardly more than statistical expectations assuming voters behave randomly. Focusing on normalised indices we show that rational players would behave differently from the in-dices predictions and propose a model that captures such strategic behaviour.
Keywords: C71; D72; 330; Banzhaf index; Shapley-Shubik index; a priori voting power; rational players; Spieltheorie; Shapley-Wert; Abstimmungsspiel; Theorie